THE INFLUENCE OF STORE ATMOSPHERE AND SOCIAL MEDIA PROMOTION ON PURCHASE DECISIONS AT COFFEE SHOP IN PEKANBARU (CASE STUDY REHAT COFFE) - Dandi, Lisman; Afwa, Awliya; Hasan, Hazwari (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
ABSTRACTThis study aims to analyze The Influence of Store Atmosphere and Social Media Promotion on Purchase Decisions at Coffee Shop in Pekanbaru (Case study Rehat Coffe). The object of this research is Rehat Coffee which is located on Jl. Sumatra No. 66b, Simpang Empat, Kec. Pekanbaru City, Pekanbaru City with a sample of 100 respondents who are buyers at Rehat Coffee. The data analysis technique uses Structural Equation Modeling using the Smart PLS version 3 application. The findings from this study note that the Store Atmosphere has a positive and significant effect on purchase decisions at Rehat Coffee. Meanwhile, Social Media Promotion has no significant effect on Purchase Decisions. Based on the determination test, it was concluded that Store Atmosphere and Social Media Promotion simultaneously influence Purchase Decisions on Rehat Coffee. This research is conducted due to the trend among the public to spend time at coffee shops. The implication of the results of this research is that the owner of Rehat Coffe can consider changing the store atmosphere and implementing other promotional strategies to increase consumer purchasing decisions.Keywords: Store Atmosphere, Social Media Promotion, Purchase Decisions, Rehat Coffee